2017
DOI: 10.2298/mpns1712377m
|View full text |Cite
|
Sign up to set email alerts
|

Eye care in mechanically ventilated critically ill adults-nursing practice analysis

Abstract: Introduction. Eye care is among basic nursing interventions in critically ill patients, but often neglected due to an ongoing focus on life threatening conditions in this group of patients. At the time being, there are no national guidelines for eye care in critically ill patients in Serbia. Aim of the study was to evident nurses? knowledge, attitudes and everyday clinical practice toward eye care in mechanically ventilated critically ill patients. Material and Methods. The study was prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The prospective study investigates the effect of body position on intraocular pressure (IOP), confirmed the prone position record highest pressure among both, investigated and healthy groups [7] . Although, there are many studies in the world focused on eye care in intensive care units, in Iraq the information on this subject is inadequate [1,2,8,9,12,14] . In Iraq also, literatures published about eye screening and care in many types of eye disease in public, there is no study yet, assess nurses' knowledge based on evidencebased practice toward eye care in ICUs [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The prospective study investigates the effect of body position on intraocular pressure (IOP), confirmed the prone position record highest pressure among both, investigated and healthy groups [7] . Although, there are many studies in the world focused on eye care in intensive care units, in Iraq the information on this subject is inadequate [1,2,8,9,12,14] . In Iraq also, literatures published about eye screening and care in many types of eye disease in public, there is no study yet, assess nurses' knowledge based on evidencebased practice toward eye care in ICUs [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Eye care is a significant aspect of the caring process of critically ill patients 1 but often neglected due to continuous focus on the life-threatening situations in this group of patients. 2 In the intensive care unit (ICU), the eyes of patients are exposed to complications such as dry eye, incomplete eyelid closure, conjunctival edema, and defects in the integrity of the cornea. 3,4 Ocular surface disorders (OSDs) affect 23-60% of ICU patients.…”
Section: Introductionmentioning
confidence: 99%